Reversed Roles? Wage and employment effects of the current crisis, employment and income distribution - Bellmann, Lutz; Gerner, Hans-Dieter (Research in Labor Economics, 2011)
In Germany, the economic crisis 2008/09 was restricted to export-oriented industries such as automotive, chemistry, and mechanical engineering and hence to industries with a high proportion of qualified employees. Therefore, we expect the most current crisis to have a reversed effect on the relative earnings position between more and less qualified in contrast to a development that favored the more qualified since the beginning of the 1980s. Our empirical study is based on the Institute for Employment Research (IAB) Establishment Panel, a representative German establishment level panel data set that surveys information from almost 16,000 personal interviews with high ranked managers.Despite the “German Job Miracle,” conditional difference-in-differences estimations to control for observed and unobserved heterogeneity reveal substantial employment reductions in establishments affected by the economic crisis. Falls in employment are strongest in plants with a relatively low proportion of qualified workers. Furthermore, our results indicate that the economic crisis is associated with a decline in wages, but only in those establishments that do not operate working time accounts. In sum, we do not find evidence for the current crisis having a reversed effect on the relative earnings position. Obviously once again, the higher qualified are better off than the lower qualifie
WiSo-Import:2015-03-26:3636